Advances in the study of the relationship between Porphyromonas gingivalis and various diseases - Zou, Qinghua; Xie, Hua; Yang, Wentai; Xu, Jiacheng; Ying, Shuyan; Liao, Xiaomin; Xie, Jun; Wu, Xiongjian; Meng, Fan (Frontiers in Cell and Developmental Biology, 2025)
The relationship between the imbalance of flora and the development of various diseases is one of the hotspots of research in recent years. A number of studies have confirmed that porphyromonas gingivalis (P. gingivalis) is strongly associated with the progression of periodontal disease, oral cancer, esophageal carcinoma, colorectal carcinoma, pancreatic cancer, Alzheimer’s disease, rheumatoid arthritis and other diseases. These diseases have a great impact on human health. Therefore, exploring the pathogenic mechanisms of P. gingivalis and the aforementioned diseases is of great significance. In this paper, we focus on the pathogenicity factors of P. gingivalis and the relationship between P. gingivalis and the progression of various diseases through different signaling pathways, so as to understand the pathogenic mechanism of P. gingivalis in a more in-depth and systematic manner.